Product availability in automatic vending machines: is it adjusted to government recommendations and student’s needs? - Gouveia, Raquel (2022)
Nutritional behavior in college/university students can be determined by a broad set of individual and environmental conditions, such as product availability in the school's facilities and their cost. Evaluating and improving food quality and availability in school facilities can be a good strategy to promote healthier eating habits among the school community. Objectives: To audit product availability in vending machines from an academic Lisbon institute and its costs, and to compare the adequacy of these products with government legislation.